Telemedicine in Pediatric Respiratory Care: Benefits, Challenges, and Future Directions (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This study explores the impact of telemedicine on pediatric respiratory care, focusing on its benefits, challenges, and future directions. A mixed-methods approach was employed, involving 150 pediatric patients with chronic respiratory conditions such as asthma and cystic fibrosis, who were randomly assigned to either telemedicine or traditional care groups. The telemedicine group used a digital platform for video consultations, remote monitoring, and health management over a 12-month period. Quantitative data on clinical outcomes, including emergency department visits and hospitalizations, were collected from electronic health records, while patient-reported outcomes were assessed through surveys. Qualitative data were gathered via semi-structured interviews with patients and caregivers. Results indicated that the telemedicine group experienced significantly fewer emergency visits and hospitalizations, higher quality of life scores, better treatment adherence, and greater patient satisfaction compared to the traditional care group. Average oxygen saturation and peak flow rates were also higher in the telemedicine group, and more frequent monitoring alerts were noted.